2004
DOI: 10.1002/ajh.10455
|View full text |Cite
|
Sign up to set email alerts
|

C1272S: A new candidate mutation in type 2A von Willebrand disease that disrupts the disulfide loop responsible for the interaction of VWF with platelet GP lb‐IX

Abstract: Most of type 2A von Willebrand disease (VWD) mutations are clustered within the A2 domain of VWF, encoded by the 3 0 region of exon 28 of the von Willebrand factor (VWF) gene. A patient with lifelong and severe bleeding diathesis and laboratory data of type 2A VWD is described. The analysis of the complete exon 28 of the VWF gene showed a 3815 GÞC change within the A1 domain, resulting in the C1272S missense mutation in a heterozygous state. The substitution was not found in 100 normal alleles also examined an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Similar results were obtained from a patient with a C1272F mutation reported by Woods et al with low basal VWF:Ag = 32 U/dl, VWF:RCo/VWF:Ag ratio < 0.15 and absent RIPA at >1.5 mg/mL ristocetin [15]. A DDAVP trial previously performed on a patient with a C1272S mutation reported by Penas et al in which platelet counts dropped from 200*10 9 L −1 to 157*10 9 L −1 at 30 min post-DDAVP treatment even though VWF:Ag, VWF:RCo, RIPA and presence of high molecular weight multimers were deficient relative to normal throughout the trial [15]. Relative to the patients reported here, DDAVP treatment of the C1272S patient only modestly reduced the platelet count indicating that perhaps the expression of the mutation was variable as has been observed with other type 2M/2A VWD patients with the same genotype within the same family [27].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results were obtained from a patient with a C1272F mutation reported by Woods et al with low basal VWF:Ag = 32 U/dl, VWF:RCo/VWF:Ag ratio < 0.15 and absent RIPA at >1.5 mg/mL ristocetin [15]. A DDAVP trial previously performed on a patient with a C1272S mutation reported by Penas et al in which platelet counts dropped from 200*10 9 L −1 to 157*10 9 L −1 at 30 min post-DDAVP treatment even though VWF:Ag, VWF:RCo, RIPA and presence of high molecular weight multimers were deficient relative to normal throughout the trial [15]. Relative to the patients reported here, DDAVP treatment of the C1272S patient only modestly reduced the platelet count indicating that perhaps the expression of the mutation was variable as has been observed with other type 2M/2A VWD patients with the same genotype within the same family [27].…”
Section: Resultssupporting
confidence: 88%
“…In agreement with our clinical data at "basal" times, the patient with a C1272R mutation reported by Lavergne et al also had low VWF:Ag = 30 U/dl, a VWF:RCo activity < 5, and absent RIPA, but a DDAVP trial was not performed [14]. Similar results were obtained from a patient with a C1272F mutation reported by Woods et al with low basal VWF:Ag = 32 U/dl, VWF:RCo/VWF:Ag ratio < 0.15 and absent RIPA at >1.5 mg/mL ristocetin [15]. A DDAVP trial previously performed on a patient with a C1272S mutation reported by Penas et al in which platelet counts dropped from 200*10 9 L −1 to 157*10 9 L −1 at 30 min post-DDAVP treatment even though VWF:Ag, VWF:RCo, RIPA and presence of high molecular weight multimers were deficient relative to normal throughout the trial [15].…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In the case reported for the patient with C1272F, plasma VWF multimer gel analysis showed an absence of high and intermediate molecular weight multimers [1]. However, only high molecular weight multimers were absent in a patient with a C1272S substitution, indicating that VWF can be secreted into the blood as low molecular weight forms [2]. Multimer studies on recombinant VWF containing C1272R and C1272G show an absence of high molecular weight multimers and an absence of both high and intermediate molecular weight species in C1458G VWF [9].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with type 2A VWD, mutations in VWF A1 and A2 domains often resulted in the loss of HMW, and sometimes intermediate MW, multimers [7], [23]. It is proposed that type 2A VWD may be divided into groups I and II, based on different molecular defects [7], [11], [21], [24].…”
Section: Discussionmentioning
confidence: 99%